Potential distribution of Notopterygium incisum Ting ex H. T. Chang and its predicted responses to climate change based on a comprehensive habitat suitability model. Issue 6 (5th March 2020) - Zhao, Zefang; Guo, Yanlong; Wei, Haiyan; Ran, Qiao; Liu, Jing; Zhang, Quanzhong; Gu, Wei
Abstract: Notopterygium incisum Ting ex H. T. Chang is a rare and endangered traditional Chinese medicinal plant. In this research, we built a comprehensive habitat suitability (CHS) model to analyze the potential suitable habitat distribution of this species in the present and future in China. First, using nine different algorithms, we built an ensemble model to explore the possible impacts of climate change on the habitat distribution of this species. Then, based on this model, we built a CHS model to further identify the distribution characteristics of N. incisum ‐suitable habitats in three time periods (current, 2050s, and 2070s) while considering the effects of soil and vegetation conditions. The results indicated that the current suitable habitat for N. incisum covers approximately 83.76 × 10 3  km 2, and these locations were concentrated in the Tibet Autonomous Region, Gansu Province, Qinghai Province, and Sichuan Province. In the future, the areas of suitable habitat for N. incisum would significantly decrease and would be 69.53 × 10 3  km 2 and 60.21 × 10 3  km 2 in the 2050s and 2070s, respectively. However, the area of marginally suitable habitat would remain relatively stable. This study provides a more reliable and comprehensive method for modelling the current and future distributions of N. incisum, and it provides valuable insights for highlighting priority areas for medicinal plant conservation and resource utilization. Abstract : Built a comprehensive habitat suitability model (CHS) for Notopterygium incisum, which constructed separately for the climate, vegetation, and soil environment demands. Climate change will intensify the destruction and fragmentation of native habitats of N. incisum, which will lead to the disappearance of suitable habitat in these areas, increasing the risk of the extinction of this species.